(untitled) (International Scientific Journal Alfraganus, 2024)
This arƟcle examines the influence of Karl Popper’s views on postposiƟvism, and explains how Popper’s views are related to the ideas of posiƟvism, neoposiƟvism, and formed as an idea that complements the above teachings from the point of view of historical development. The role and importance of Popper’s views in modern philosophy and the aƫtude towards him in his Ɵme are analyzed.